2014
DOI: 10.1093/intimm/dxu088
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a vascular endothelial cell-reactive type II NKT cell clone from a rat model of autoimmune vasculitis

Abstract: We previously generated a rat model that spontaneously developed small vessel vasculitis (SVV). In this study, a T cell clone reactive with rat vascular endothelial cells (REC) was established and named VASC-1. Intravenous injection of VASC-1 induced SVV in normal recipients. VASC-1 was a TCRαβ/CD3-positive CD4/CD8 double-negative T cell clone with expression of NKG2D. The cytokine mRNA profile under unstimulated condition was positive for IL-4 and IFN-γ but negative for IL-2 and IL-10. After interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In a mouse bone marrow transplantation model, donor type II NKT cells inhibit graft-vs.-host disease via releasing IL-4 ( 37 ). In a rat model, activating type II NKT cells with SCP2 peptide promotes the inflammatory response through production of inflammatory cytokines IL-5 and IL-6 ( 38 ). In an iNKT cell-deficient (Jα18 −/− ) mouse model, Sagami et al found adoptive transfer of type II NKT cells exacerbated DSS-induced colitis ( 39 ).…”
Section: The Biology Of Innate T Cellsmentioning
confidence: 99%
“…In a mouse bone marrow transplantation model, donor type II NKT cells inhibit graft-vs.-host disease via releasing IL-4 ( 37 ). In a rat model, activating type II NKT cells with SCP2 peptide promotes the inflammatory response through production of inflammatory cytokines IL-5 and IL-6 ( 38 ). In an iNKT cell-deficient (Jα18 −/− ) mouse model, Sagami et al found adoptive transfer of type II NKT cells exacerbated DSS-induced colitis ( 39 ).…”
Section: The Biology Of Innate T Cellsmentioning
confidence: 99%
“…Liao et al demonstrated that the disordered regulation of CD1d-restricted type II NKT cells could cause the spontaneous development of colitis in CD1d transgenic mice (8). In addition, we have shown that proinflammatory autologous vascular endothelial cell-reactive CD1d-restricted type II NKT cells were involved in the development of vasculitis in rats (9). Recently, we identified P 518-532 of rat sterol carrier protein 2 (rSCP2 518-532 ), FFQGKLKIAGNMGLA, as the epitope, which was recognized by one such CD1d-restricted type II NKT cell (10).…”
mentioning
confidence: 51%
“…Terabe et al showed that CD1d-restricted type II NKT cells were essential for the down-regulation of tumor immunosurveillance in mice (7). In addition, we have shown that proinflammatory autologous vascular endothelial cell-reactive CD1d-restricted type II NKT cells were involved in the development of vasculitis in rats (9). Liao et al demonstrated that the disordered regulation of CD1d-restricted type II NKT cells could cause the spontaneous development of colitis in CD1d transgenic mice (8).…”
mentioning
confidence: 72%
“…More recently, our group has revealed the involvement of pro-inflammatory type II NKT cells that are reactive with the endogenous SCP2 peptide in the pathogenesis of small vessel vasculitis in rats ( 25 , 62 ) (Figure 1 B). CD1d-restricted type II NKT cells activated by the SCP2 peptide function to enhance inflammation by producing pro-inflammatory cytokines.…”
Section: Involvement Of Cd1d-restricted Type II Nkt Cells In Immune-rmentioning
confidence: 98%